In vivo, in vitro and in silico anticancer investigation of fullerene C60 on DMBA induced breast cancer in rats - Beyaz, Seda; Aslan, Abdullah; Gok, Ozlem; Uslu, Harun; Agca, Can Ali; Ozercan, Ibrahim Hanifi (Pergamon-Elsevier Science Ltd, 2022)
Aims: The aim of the study was to determine the protective and therapeutic effect of fullerene C-60 nanoparticle on DMBA-induced breast cancer in rats.& nbsp;Main methods: In vitro cell viability was determined by the WST-1 test. In vivo analysis was performed in female Wistar Albino rats. The expression of caspase-3, Bcl-2, Nrf-2, NF-kappa B, TNF-alpha, COX-2, p53, IL-6, IL-1 alpha ve p38 alpha (MAPK) proteins were assessed by western blotting. Furthermore, malondialdehyde (MDA), glutathione (GSH), catalase activity (CAT), total protein levels and DNA damage were investigated. In addition, tissues were evaluated by histopathologically. In in silico analysis, the binding affinities of the fullerene C-60 nanoparticle to transcription factors such as caspase-3, Bcl-2, Nrf-2, NF-kappa B, TNF-alpha, COX-2, VEGF and Akt were demonstrated by molecular docking.& nbsp;Key findings: Treatment of MCF-7 cells at various concentrations of fullerene C-60 (0.1 to 100 mg/ml) inhibited cell viability in a dose dependent manner. Fullerene C60 treated rats exhibited considerable increase in the level of caspase-3 while decrease in the level of pro-survival protein Bcl-2. Bcl-2, NF-kappa B, TNF-alpha, COX-2, IL-6, IL-1 alpha and p38 alpha (MAPK) protein expression levels and malondialdehyde (MDA) levels were decreased in the C-60 + DMBA groups compared to the DMBA group. It was observed that caspase-3, Nrf-2 and p53 protein expression levels, glutathione (GSH) level, catalase activities (CAT) and total protein levels increased significantly which was further confirmed through the resulting DNA fragmentation.& nbsp;Significance: In silico assays, fullerene C-60 has been observed to have similar affinity to some crystal ligands, especially against cancer.
Keywords: Apoptosis; Breast cancer; DMBA; Fullerene C-60; p53